Circulating Exosomal miR-150-5p and miR-99b-5p as Diagnostic Biomarkers for Colorectal Cancer - Zhao, Ya jing; Song, Xingguo; Niu, Limin; Tang, Youyong; Song, Xianrang; Xie, Li (Frontiers in Oncology, 2019)
Background: Circulating exosomal miRNAs are potential non-invasive biomarkers for colorectal cancer. The present study aimed to validate the novel sensitive and specific exosomal miRNA biomarkers for diagnosing colorectal cancer (CRC). Patients and Methods: Exosomes isolated from the serum of CRC patients and healthy donors by ultracentrifugation were characterized using TEM, qNano, and immunoblotting. The exosomes from 2 healthy donors and 4 CRC patients were subjected to RNA isolation and miRNA sequencing. The differently expressed miRNAs from 165 primary CRC patients and 153 healthy donors were substantiated by RT-qPCR. Results: The RNA-sequence data analysis revealed that 29 exosomal miRNAs (20 downregulated and 9 upregulated) with >1.5-fold difference between CRC patients and healthy donors were selected. The serum exosomal miR-99b-5p and miR-150-5p levels were significantly downregulated in CRC patients as compared to healthy donors (p < 0.0001 and p < 0.0001, respectively) and benign disease (p = 0.009 and p < 0.0001, respectively). The expression levels of exosomal miR-99b-5p and miR-150-5p were significantly decreased in early CRC patients as compared to healthy donors (p < 0.0001 and p < 0.0001, respectively). The expression levels of exosomal miR-99b-5p and miR-150-5p were significantly increased postoperatively (p = 0.0058 and p < 0.0001, respectively). Conclusions: The present study demonstrated that serum exosomal miRNAs are promising, sensitive, specific, and non-invasive diagnostic biomarkers for CRC. Impact: This is the first study to specifically identify exosomal miR-99b-5p and miR-150-5p associated with CRC. This study, therefore, might deepen the understanding of tumor-derived exosomes for CRC diagnosis.